Strategic integration of logistical support for enhanced contract management and fleet operations efficiency in The Royal Malaysian Navy - Azizi, Ahmad Sarkawi (2024)
The effectiveness of fleet operations in the Royal Malaysian Navy (RMN) has been affected by several issues, including delays in refit programs, costly delays in spare parts delivery, procurement process leakages, and integrity issues in the RMN. These difficulties are closely linked to contract management in the RMN. The aim of this study is to investigate the strategic integration between logistical support factors and enhanced contract management towards the RMN fleet operation efficiency. A quantitative survey was distributed to RMN Supply & Secretariat Officers located all over Malaysia. A total of 204 officers responded through a simple random sampling method. The data were analyzed using Statistical Package for the Social Science version 25 and Partial Least Squares Structural Equation Modelling version 3. The result demonstrated that there was no significant association between financial support and effective contract management. The result then shows a significant and positive correlation between leadership support and effective contract management. In addition, the findings reveal a significant and positive relationship between contract compliance and effective contract management. There is a significant positive relationship between technological support and effective contract management. Finally, contracting officer competency significantly moderates the relationship between technological support and effective contract management. The findings from this study suggest that to establish an optimal procurement and contract management procedure, RMN must apply compelling technological support on contracting officers’ skills as well as establish a Contract Management Office, Project Management Review, and Supply Working Group to improve efficiency, cost-effectiveness, and good procurement outcomes. Future studies should focus on mixed-mode approaches to provide a comprehensive understanding of effective contract management in the defense industry